Mistaken identity: a new Spathiphyllum (Araceae) from Veracruz, Mexico - Díaz Jiménez, Pedro; Pérez-Farrera, Miguel Ángel; Hentrich, Heiko; Gómez-Domínguez, Héctor; Ameca-Juárez, Erasmo Óscar; Aguilar-Rodríguez, Pedro A. (Phytotaxa, 2021)
The genus Spathiphyllum is represented in Mexico by 11 species, four of which are registered for the state of Veracruz. As a result of the revision of material collected in Los Tuxtlas, Veracruz, in addition to a detailed review of herbarium specimens, and comparison to individuals collected at and the type locality of Spathiphyllum cochlearispathum, we determined that the Spathiphyllum species identified as S. cochlearispathum in the Gulf of Mexico corresponds to a different species, not previously designated. The new species, Spathiphyllum croatii, is described taxonomically, illustrated, and compared with S. cochlearispathum.